SISTSISTEM INFORMASI ABSENSI DAN PENGGAJIAN KARYAWAN DI PT.SELIM ELEKTRO BERBASIS WEBEM INFORMASI INVENTORY BARANG MENGGUNAKAN METODE FIRST-IN FIRST-OUT (FIFO) BERBASIS WEB (STUDI KASUS PT. RIYANA CIPTA PANGAN INDONESIA) (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2023)
Selim Electro is a company engaged in assembling Wire harness spare parts which in data processing are still manual using the help of Ms. software. Office excel. the system that is currently running is still manual, starting from attendance data that must be recapitulated one by one and salary calculations that are still manual so that there will be problems with the results of calculating employee salaries. The research method used is descriptive analysis method, which is research that is intended to investigate a condition, situation, or other event, then the results will be presented in the form of a research report. The system design method used is UML as a translator of the flow of the information system. And also the waterfall method in system development. Using the PHP programming language combined with MySQL as a database design, and the CodeIgniter Framework as an interface designer. The results of the creation of this system are expected to help staff and admin performance processes to be more effective, reporting data will be more effective because employee data entered will be directly stored in the Information System. (Oktavia et al., 2019).